Keterampilan Interpersonal Dalam Berkomunikasi Tatap Muka - Muhammad AL Fazri; Indry Anggraini Putri; Suhairi Suhairi (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
Interpersonal communication can be defined as the ability to connect between humans as a form of verbal communication. Interpersonal communication can also be used to help build relationships with other people in different situations. Attitudes such as eye contact, body movements and hand gestures are also part of interpersonal communication. Interpersonal communication involves eye-to-eye communication in an appropriate and purposeful manner. The language used in the interpersonal communication process can describe communication patterns, management, personality and actions. Therefore, expertise in the use of language and interpersonal communication can help a person to better understand social situations and act and solve problems in accordance with existing environmental conditions.